Local performance of six clonal alien species differs between native and invasive regions in Germany and New Zealand. (29th August 2013) - Beckmann, Michael; Bruelheide, Helge; Erfmeier, Alexandra
Abstract Exotic plant invasions are widely observed to have strong biogeographic patterns with invasive species occurring at higher abundances in their introduced range when compared with their native range. However, only few field studies have validated this assumption by comparing plant populations of multiple species in their native and introduced ranges and have evaluated to what extent changes in sexual and clonal reproduction potentially have contributed to the success of plant invasions. Here, we present the results of a comparative field study in both the native (Germany) and the introduced (New Zealand, NZ) ranges of six clonal plant species with different invasive status: Achillea millefolium L., Pilosella officinarum Vaill., Hypericum perforatum L., Prunella vulgaris L., Leucanthemum vulgare Lam. and Lotus pedunculatus Cav. We hypothesized that all six species show better performance in introduced NZ than in native German populations and tested if population structures investigated at different scales provide a useful tool to identify differences between native and introduced occurrences. In 10 populations per species and country we assessed plant density and flowering proportion at the population scale and around individual plants, thereby identifying the 'crowdedness' of the populations. Furthermore, we collected individual plants and determined the number of attached clonal organs and plant biomass. For all six species crowdedness in NZ populations was higher than in German populations. Additionally, overall population density of four species and the production of clonal organs (expressed as total number or per biomass ratio) of three species were higher in NZ than in Germany. When measured around individual plants, the flowering proportion was higher in native German populations of Pilosella officinarum, Hypericum perforatum and Leucanthemum vulgare. Although the study species differed in their invasive status, our findings show that for all six species performance was better in introduced than in native populations. Furthermore, this study emphasizes that multiple measures of plant performance, different spatial scales and differences among species should be taken into account when trying to identify biogeographic differences in the performance of weed species.